The Impact of Exercises in the Lactic Effort in Developing the Rapid Ability and Concentration of Hexokinase in the Blood in Young Basketball Players - Sajit, Hussein Munati; Obaid , Raed Mohsen; Mohamed, Mohamed Moussa (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to identify the effect of exercise in the lactic effort in developing the rapid ability and concentration of hexokines in the blood among young basketball players. The experimental method was used in the two groups (experimental and control) After and before the test for its suitability of the nature of the problem’s study. While the research community has identified the young players in the Talent Center in Baghdad, who were aged 16-17 years, for the training season 2019, The researchers has prepared several exercises with anaerobic effort, that the period of application of the exercises was in the time of special preparation which has taken (8) weeks by 3 units per week. The training method was used is high-intensity vocational training and repetitive training (85 - 95%) from the maximum intensity of player performance. The most important conclusions were that the anaerobic exercises that the researcher was used led to the development of some physical capabilities (rapid ability), caused an effect in the concentration of hexokinase in the blood.